Gender Differences in Pain-Physical Activity Linkages among Older Adults: Lessons Learned from Daily Life Approaches - Amy Ho; Maureen C. Ashe; Anita DeLongis; Peter Graf; Karim M. Khan; Christiane A. Hoppmann (Pain Research and Management)
Background. Many older adults know about the health benefits of an active lifestyle, but, frequently, pain prevents them from engaging in physical activity. The majority of older adults experience pain, a complex experience that can vary across time and is shaped by sociocultural factors like gender. Objectives. To describe the time-varying associations between daily pain and physical activity and to explore differences in these associations between women and men. Methods. One hundred and twenty-eight community-dwelling older adults aged 65 years and older were asked to report their pain levels three times daily over a 10-day period and wear an accelerometer to objectively capture their daily physical activity (step counts and minutes of moderate to vigorous physical activity). Results. Increased daily step counts and minutes of moderate to vigorous physical activity were associated with increased daily pain, especially among women. Confirming past literature and contrasting findings for daily pain reports, overall pain levels across the study period were negatively associated with minutes of moderate to vigorous physical activity. Conclusions. Findings highlight that pain is significantly associated with physical activity in old age. The nature of this association depends on the time scale that is considered and differs between women and men.